19x*x-9x-100=135

Simple and best practice solution for 19x*x-9x-100=135 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19x*x-9x-100=135 equation:


Simplifying
19x * x + -9x + -100 = 135

Multiply x * x
19x2 + -9x + -100 = 135

Reorder the terms:
-100 + -9x + 19x2 = 135

Solving
-100 + -9x + 19x2 = 135

Solving for variable 'x'.

Reorder the terms:
-100 + -135 + -9x + 19x2 = 135 + -135

Combine like terms: -100 + -135 = -235
-235 + -9x + 19x2 = 135 + -135

Combine like terms: 135 + -135 = 0
-235 + -9x + 19x2 = 0

Begin completing the square.  Divide all terms by
19 the coefficient of the squared term: 

Divide each side by '19'.
-12.36842105 + -0.4736842105x + x2 = 0

Move the constant term to the right:

Add '12.36842105' to each side of the equation.
-12.36842105 + -0.4736842105x + 12.36842105 + x2 = 0 + 12.36842105

Reorder the terms:
-12.36842105 + 12.36842105 + -0.4736842105x + x2 = 0 + 12.36842105

Combine like terms: -12.36842105 + 12.36842105 = 0.00000000
0.00000000 + -0.4736842105x + x2 = 0 + 12.36842105
-0.4736842105x + x2 = 0 + 12.36842105

Combine like terms: 0 + 12.36842105 = 12.36842105
-0.4736842105x + x2 = 12.36842105

The x term is -0.4736842105x.  Take half its coefficient (-0.2368421053).
Square it (0.05609418284) and add it to both sides.

Add '0.05609418284' to each side of the equation.
-0.4736842105x + 0.05609418284 + x2 = 12.36842105 + 0.05609418284

Reorder the terms:
0.05609418284 + -0.4736842105x + x2 = 12.36842105 + 0.05609418284

Combine like terms: 12.36842105 + 0.05609418284 = 12.42451523284
0.05609418284 + -0.4736842105x + x2 = 12.42451523284

Factor a perfect square on the left side:
(x + -0.2368421053)(x + -0.2368421053) = 12.42451523284

Calculate the square root of the right side: 3.524842583

Break this problem into two subproblems by setting 
(x + -0.2368421053) equal to 3.524842583 and -3.524842583.

Subproblem 1

x + -0.2368421053 = 3.524842583 Simplifying x + -0.2368421053 = 3.524842583 Reorder the terms: -0.2368421053 + x = 3.524842583 Solving -0.2368421053 + x = 3.524842583 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2368421053' to each side of the equation. -0.2368421053 + 0.2368421053 + x = 3.524842583 + 0.2368421053 Combine like terms: -0.2368421053 + 0.2368421053 = 0.0000000000 0.0000000000 + x = 3.524842583 + 0.2368421053 x = 3.524842583 + 0.2368421053 Combine like terms: 3.524842583 + 0.2368421053 = 3.7616846883 x = 3.7616846883 Simplifying x = 3.7616846883

Subproblem 2

x + -0.2368421053 = -3.524842583 Simplifying x + -0.2368421053 = -3.524842583 Reorder the terms: -0.2368421053 + x = -3.524842583 Solving -0.2368421053 + x = -3.524842583 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2368421053' to each side of the equation. -0.2368421053 + 0.2368421053 + x = -3.524842583 + 0.2368421053 Combine like terms: -0.2368421053 + 0.2368421053 = 0.0000000000 0.0000000000 + x = -3.524842583 + 0.2368421053 x = -3.524842583 + 0.2368421053 Combine like terms: -3.524842583 + 0.2368421053 = -3.2880004777 x = -3.2880004777 Simplifying x = -3.2880004777

Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.7616846883, -3.2880004777}

See similar equations:

| 64x-8xy=0 | | -7(x+12)=-91 | | 50-3x=90 | | 6x+16=106 | | 4x^2+4y^2+6x+8y-5=0 | | 3*(x+12)+5x=92 | | 6x+16 = 106 | | 7.4x+17=76.2 | | -6x-8 = -50 | | 2.7x+18=63.9 | | 10x+17=177 | | -11x+17=-126 | | 2x-15 = -19 | | 25x+7=207 | | 3(2x-4)+8=6 | | 2x/3=(X-10)/4 | | 7w+14=14 | | 7w+14=4 | | 19-5x=-15 | | 11x+13=200 | | -5x+16=-54 | | 16m^2-81(m-3)(m-3)=0 | | 1+3x=-3+9x | | 3p+12=6p-24 | | 16=25 | | 5x-0.6x=7.48 | | 2.9=8.3x | | .5x=.4+.4x | | -6x+9x=-15 | | 12-3x=-8.7 | | 3.6(x+5)=50.4 | | w/4=w/2=1/4=W |

Equations solver categories